Pengalaman Pembelajaran Jarak Jauh Mahasiswa : Peran Self-Regulated Online Learning Dan Persepsi Dukungan Sosial Terhadap Motivasi Akademik - Rahmadini, Rizqika; Salim, Rose Mini Agoes (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
College students have higher academic requirements and responsibilities compared to previous education levels. Being academically motivated is very important so that success at college can be achieved. However, remote learning due to COVID-19 pandemic rises new challenges for college students in maintaining their academic motivation level. Previous research has shown that self-regulated learning (SRL) and perceived social support have a significant positive relationship with academic motivation. This study aims to determine the effect of self-regulated online learning (SROL) which is SRL in an online learning environment, as well as perceived social support on the academic motivation of college students who participated in remote learning, either fully online or blended learning between online and offline. A total of 162 undergraduate and postgraduate students were involved in this study. Academic motivation is measured through the Academic Motivation Scale (AMS); SROL is measured through the Self-Regulated Online Learning (SROL) scale; and perceived social support is measured through the Multidimensional Scale of Perceived Social Support (MSPSS). The results of multiple linear regression analysis indicate that SROL and perceived social support together have a positive and significant effect of 35.9% on academic motivation. Furthermore, SROL was found to make a greater contribution to the academic motivation of college students participating in remote learning compared to perceived social support.